The Relationship between Inclusive Education Policy with Teachers’ Attitude to Children with Special Needs at Inclusive School - Sutarni, Sutarni; Yusuf, Munawir; Anggrellanggi, Arsy (Department of Special Education, 2022)
The aim of this study is to know the relationship between teachers’ understanding to inclusive education policy with teachers’ attitude to children with special needs at inclusive school in Pati. According to the aim, this study used correlational quantitative approach. The subject of this study were 40 teachers of inclusive school in Pati. The sampling technique used was simple random sampling technique. The data collection technique used was likert model scale instrument. The analysis result indicates the hypothesis is accepted, it means that there is a significant relation between the understanding of inclusive education policy with the teachers’ attitude to children with special needs by value of 2,860 > 2,061 ( > ) and significant value of < 0,05 (0,007 < 0,05). Correlation coefficiency value (R) of this study is 0,421. It means that relationship betweem teachers’ understanding to inclusive education policy with teachers’ attitude to children with special needs in Pati has a fairly strong relationship. The precentage of the influence of contribution which has understanding of inclusive education policy to the teachers’ attitude to children with special needs is 17,7% which indicates by determination coefficient () of 0,177, meanwhile the rest of 82,3% is influenced by other not examined factors.